2014
DOI: 10.1176/appi.ajp.2013.12081103
|View full text |Cite
|
Sign up to set email alerts
|

A Genome Scan for Loci Shared by Autism Spectrum Disorder and Language Impairment

Abstract: Objective The authors conducted the first genetic linkage study of families that segregate both autism and specific language impairment to find common communication impairment loci. The hypothesis was that these families have a high genetic loading for impairments in language ability, thus influencing the language and communication deficits of the family members with autism. Comprehensive behavioral phenotyping of the families also enabled linkage analysis of quantitative measures, including normal, subclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…Here, the point-wise p value was estimated by performing 11,000 phenotype permutations and determining how many null replicates exceeded the observed PPL in the main linkage analysis. These data are consistent with the genome-wide cut-off from other studies [29][30][31] requiring a PPL of at least 27% and a posterior probability of association (PPLD) to be at least 9% for nominal association of p < 0.001.…”
Section: Linkage/association Analysis Methodssupporting
confidence: 90%
“…Here, the point-wise p value was estimated by performing 11,000 phenotype permutations and determining how many null replicates exceeded the observed PPL in the main linkage analysis. These data are consistent with the genome-wide cut-off from other studies [29][30][31] requiring a PPL of at least 27% and a posterior probability of association (PPLD) to be at least 9% for nominal association of p < 0.001.…”
Section: Linkage/association Analysis Methodssupporting
confidence: 90%
“…For example, some work attempts to categorise or quantify types of language and communication profiles and/or phenomena that may be presented by people diagnosed with ASD (e.g., Kwok et al 2015). A greater body of work uses experimental paradigms to attempt to identify language-oriented cognitive, neurophysiological or genetic differences in people diagnosed with ASD, and then examine potential associations between these and language performance by such individuals (e.g., Boucher et al 2008;Bartlett et al 2014).…”
mentioning
confidence: 99%
“…Coon et al (2010) performed linkage analyses for SRS in 64 multiplex families and identified significant non-parametric linkage to chr15q13.3 (LOD 3.64) and suggestive linkage to chr7q31.1-q32.3 (LOD 2.91) (15). In a collection of 70 families segregating ASD with or without language impairment, Bartlett et al (2014) reported strong linkage to SRS as a quantitative trait at chr15q26.2-26.3 and as a dichotomous trait at chr14q32.2-32.33 (34). These studies observed little or no evidence for linkage on chromosome 8p21.3 or 8q24.22; we observe a similar lack of signal in their regions of interest.…”
Section: Discussionmentioning
confidence: 99%